BUKU RAMAH CERNA BERBASIS HUMAN SECURITY UNTUK PENGUATAN PROFIL PELAJAR PANCASILA DI SEKOLAH DASAR - Sani Aryanto; Putri Ayuni Agustina; Meyke Erlianda; Ade Putri Puspitasari; Anggreni Eklecia Silaen (Journal of Professional Elementary Education, 2023)
Developing the principles of human security and internalizing the values of the Pancasila Student Profile as the basis for developing decodable books become novelties for this research. Therefore, the purpose of this library research is to provide a contextual and conceptual overview of decodable books based on human security in an effort to strengthen the Pancasila Student Profile for students in the Early Readers category in elementary schools. This research used the library research method to uncover several findings from the research, including: (1) The Nature of Decodable Books; (2) Classification of Decodable Books and Leveled Books; (3) Characteristics of Decodable Books for Early Readers Category (B1); (4) The Concept of Human Security in Elementary School; and (5) Internalization of Pancasila Student Profile Values in the Context of Developing Decodable Books in Elementary Schools. This research method is considered an appropriate method for supporting the meta-analysis results of several relevant previous studies, supported by various theoretical studies from various sources and government policies that support the focus of this research. The results of the research conducted revealed that explicit book development can be known through BSKAP No. 030/P/2022 Concerning Guidelines for Leveling Book, although there has not been a comprehensive discussion. The results of this research produce propositions that can be followed up in other, more complex research